Izin Usaha E-Commerce di Indonesia Perspektif Maqashid Syariah - Listiani; Agus Salim Ferliadi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to determine the suitability of the regulation of E-Commerce business licenses in Indonesia from the perspective of maqashid sharia by revealing three crucial aspects of the regulation of e-commerce business licenses. First, I will discuss the development of e-commerce in Indonesia. Second, about the regulations governing e-commerce business licenses. Third, the perspective of Maqasaid Sharia on the regulations of the Minister of Trade, significantly the articles that examine e-commerce business licenses. This research method is a literature that uses a normative juridical approach. Primary data sources involve laws, regulations, and relevant regulations. Secondary data sources involve scientific literature and e-commerce statistical data in publications from Kominfo's official website and other online sources related to this study. Based on the study, it is known that there are five e-commerce platforms in great demand by the Indonesian people: Shopee, Tokopedia, Lazada, Bukalapak, and Blibli. Where each platform has differences in electronic transaction practices and business license practices. The results of this study show that E-Commerce business licenses following Maqashid Sharia have a broader impact on society. Maqashid Sharia, which protects religion, soul, mind, descendants, and property, is the basis for developing a regulatory framework, especially property protection, that supports digital trading activities. Thus, e-commerce business permits based on maqashid sharia are beneficial for individuals and society at large.